DIGITAL EDUCATION AND ITS ROLE IN MODERN LEAR (Ustozlar uchun, 2025)
This article explores the growing role of digital education in transforming teaching and learning processes in the 21st century. It highlights how online platforms, e-learning technologies, and artificial intelligence tools have influenced student engagement, educational accessibility, and personalized learning. The study emphasizes both the advantages and challenges of digital education: while technology improves global access, motivation, and interactive learning, it also creates issues related to the digital divide and reduced face-to-face communication. The article concludes that digital education is shaping a new model of learning that reflects the needs of the digital age and prepares learners for future skills.